The Potential of Fumyco (Arbuscular Mycorrhiza Fungi) in Increasing The Growth of Oil Palm (Elaeis guineensis Jacq.) Seedling in Nursery - Hazra, Fahrizal; Nur Istiqomah, Fatimah; Nurul Fadilla, Ardina (Jurnal Penelitian Kelapa Sawit, 2023)
Oil palm (Elaeis guineensis Jacq.) is one of the vegetable oil-producing plantation crops that is a leading commodity in Indonesia. The application of biological fertilizers is an alternative to help improve the growth of oil palm seedlings. This study aimed to analyze the effect of the use of mycorrhizal biofertilizers on the growth of oil palm plants in the Nursery. The study used a single-factor Completely Randomized Design (CRD) with 6 treatment levels and 10 replications. Biofertilizer test treatments based on Ministerial Regulation No.1 of 2019 were control (A); standard NPK fertilizer (15-15-15) 2,5 g (B); 20 gr biofertilizer (C); 1 standard NPK+20 g biofertilizer (D); 3/4 standard NPK+20 g biofertilizer (E); and 1/2 standard NPK+20 g biofertilizer (F). The application of mycorrhizal biofertilizer either alone or in combination with various doses of NPK can increase the height, diameter, number of leaves, dry weight (BK) of roots and crown of oil palm seedlings aged 12 weeks after planting (MST) compared to the control and standard NPK fertilizer. The Relative Agronomic Effectiveness (RAE) value in the 3/4 NPK+20 g mycorrhizal biofertilizer treatment showed the most effective results agronomically with the result height 504,63%, diameter 758,82%, number of leave 504,62%, shoots dry weight 378,33%, dan root dry weight 291,81%.